Significant Effect of Pore Sizes on Energy Storage in Nanoporous Carbon Supercapacitors. Issue 23 (6th April 2018) - Young, Christine; Lin, Jianjian; Wang, Jie; Ding, Bing; Zhang, Xiaogang; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; Hossain, Shahriar A.; Khan, Junayet Hossain; Ide, Yusuke; Kim, Jeonghun; et al.
Abstract: Mesoporous carbon can be synthesized with good control of surface area, pore‐size distribution, and porous architecture. Although the relationship between porosity and supercapacitor performance is well known, there are no thorough reports that compare the performance of numerous types of carbon samples side by side. In this manuscript, we describe the performance of 13 porous carbon samples in supercapacitor devices. We suggest that there is a "critical pore size" at which guest molecules can pass through the pores effectively. In this context, the specific surface area (SSA) and pore‐size distribution (PSD) are used to show the point at which the pore size crosses the threshold of critical size. These measurements provide a guide for the development of new kinds of carbon materials for supercapacitor devices. Abstract : Designing supercapacitor materials : Several porous carbon samples were tested in supercapacitor devices. There is a "critical pore size" at which guest molecules can pass through the pores effectively. Measurements of specific surface area (SSA) and pore‐size distribution (PSD) provide a guide for the development of new kinds of carbon materials for supercapacitor devices (see figure).